Approaches to Building Teacher-Parent Cooperation - Franc Cankar; Tomi Deutsch; Sonja Sentočnik (Center for Educational Policy Studies Journal)
The purpose of this study was to explore the areas of cooperation in which parent and teacher expectations were the same and where they differed. Data were obtained from a sample of 55 randomly selected primary schools. We analyzed school-to home communications, parental influence on school decisions, and parent involvement in different school activities. At the same time, we also explored building cooperation among the teachers, students, and their parents, within the framework of the program ‘Reading and Conversation’. The findings indicated that the third- and ninth- grade lead teachers were mostly in agreement about the importance of parent involvement and as such represented a fairly homogenous group. The third-grade lead teachers were more open about actual involvement of parents in instruction than their ninth-grade colleagues, who were more cautious and restrained. In contrast to the lead teachers who represented a relatively narrow professional group, parents’ views were much more diverse. Parental education was the best predictor of their readiness to become involved in the life and work of their children’s school. Whether the area in which the families lived was urban or suburban did not make any difference. The evaluation of the one-year ‘Reading and Conversation’ programme revealed increases in parents’motivation to collaborate with the school as a consequence of the program’s approach to work, as well as improvement in mutual relationships and dialogue.